Relationship of Physical Activity to Primary Dysmenorrhea - M.Pemberdi Intasir; Een Sumarni (Universitas Andalas, 2022)
This study aims to determine the relationship between physical activity and primary dysmenorrhea. The method used in this study is a cross sectional study. A sample of 30 Biology Education students at Raja Ali Haji Maritime University class of 2021 used a purposive sampling technique. To measure primary dysmenorrhea using the McGill`s questionnaire, the IPAQ (International Physical Activity Questionnaire) questionnaire measures physical activity. Data analysis uses Chi Square. The results of the analysis of physical activity on primary dysmenorrhea showed a p value of 0.0 (p <0.05). Thus it can be concluded that there is a significant relationship between physical activity and primary dysmenorrhea in female students.